Dynamic Environmental Niches of Marine Invasive Species Over 200 Years - Chunlong Liu; Zeli Ruan; Jiayuan Xie; Jonathan M. Jeschke; Lise Comte; Julian D. Olden; Yunwei Dong; Jiansong Chu; Bin Kang; Brian Leung (Ecology Letters, 2025)
Anticipating the risk of species invasions in new geographical regions remains fundamental to conservation. One critical assumption is that species' environmental niches remain stable under changing environments. If native environmental drivers predict introduced distributions, we would expect high overlap in niche space between native and introduced ranges, with introduced niche increasingly resembling their native niche over time. We quantified changes in species' occupied niche space across 200 years of invasion records, for 778 marine invaders at the global scale. For species in introduced ranges, the majority of their native niche space remained unfilled, even after two centuries. As expected, overlap between native and introduced niche spaces increased with time since invasion. However, niche overlap remained low on average, never exceeding 20% across species. Our results suggest that native environmental drivers will largely fail to predict introduced species ranges in marine ecosystems within policy‐relevant (decadal) time frames.